2017
DOI: 10.1111/cas.13316
|View full text |Cite
|
Sign up to set email alerts
|

Role of zoledronic acid in oncolytic virotherapy: Promotion of antitumor effect and prevention of bone destruction

Abstract: Osteosarcoma is an aggressive malignant bone tumor that causes bone destruction. Although tumor‐specific replicating oncolytic adenovirus OBP‐301 induces an antitumor effect in an osteosarcoma tumor, it cannot prevent bone destruction. Zoledronic acid (ZOL) is a clinically available agent that inhibits bone destruction. In this study, we investigated the potential of combination therapy with OBP‐301 and ZOL against osteosarcomas with bone destruction. The antitumor activity of OBP‐301 and ZOL in monotherapy or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…This process maintains a balance between the death and survival of cells and tissues [ 56 ]. It is demonstrated that ZA induces the apoptosis of osteoclasts through inhibition of the farnesyl pyrophosphate synthase (FPPS)-mediated mevalonate pathway, and induction of reactive oxygen species (ROS)-mediated apoptosis [ 24 , 39 , 57 , 58 ].…”
Section: Induction Of Apoptosis Of Osteoclastsmentioning
confidence: 99%
See 2 more Smart Citations
“…This process maintains a balance between the death and survival of cells and tissues [ 56 ]. It is demonstrated that ZA induces the apoptosis of osteoclasts through inhibition of the farnesyl pyrophosphate synthase (FPPS)-mediated mevalonate pathway, and induction of reactive oxygen species (ROS)-mediated apoptosis [ 24 , 39 , 57 , 58 ].…”
Section: Induction Of Apoptosis Of Osteoclastsmentioning
confidence: 99%
“…Furthermore, it is demonstrated that the treatment of ZA with other chemotherapies in children leukemia related osteonecrosis is safe and tolerant [ 118 ]. Combination therapy with ZA and tumor-specific replicating oncolytic adenovirus DBP-301 significantly inhibits tumor-mediated osteoclast activation, tumor growth and bone destruction via suppression of Mcl-1 [ 24 ]. In addition, ZA and R115777 (Zarnestra) are synergistic in inducing both growth inhibition and apoptosis in cancer cells by disruption of Ras-dependent Erk and Akt survival pathways and consequent Bcl-related proteins-dependent apoptosis [ 76 , 78 ].…”
Section: Anticancer Effects Of Zamentioning
confidence: 99%
See 1 more Smart Citation
“…OBP-301 enhances the sensitivity of osteosarcoma cells to the chemotherapeutic reagents doxorubicin and cisplatin [54]. Regarding the molecular mechanism underlying OBP-301's enhancement of chemosensitivity, adenoviral E1A protein upregulates the expression of E2F1 and microRNA-29, leading to suppression of the anti-apoptotic myeloid cell leukemia 1 protein [54,55]. Thus, the combination of OBP-301 and chemotherapy is a promising antitumor strategy for the treatment of osteosarcoma.…”
Section: Combination Therapy With Obp-301 and Chemotherapeutic Reagenmentioning
confidence: 99%
“…Zoledronic acid (ZOL) is a third-generation bisphosphonate that is used clinically for suppressing bone destruction in patients with metastatic bone tumors [59]. Combination therapy with OBP-301 and ZOL efficiently suppresses bone destruction caused by OBP-301-resistant osteosarcoma cells [55]. Moreover, Conry et al showed that ZOL treatment improves the progression-free survival in patients with metastatic osteosarcoma [60].…”
Section: Combination Therapy With Obp-301 and Chemotherapeutic Reagenmentioning
confidence: 99%